German minority in Ukraine. An outline of history = Mniejszość niemiecka na Ukrainie. Zarys dziejów - Kaźmierczak-Pec, Dorota (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article German minority in Ukraine. An outline of history is a synthetic work dedicated to the history of German colonization of Ukrainian territories, with special focus on the "Golden Age" of German colonization in southern Ukraine during the reign of Tzarina Catherine II, and the interwar period. The paper presents the population size, distribution, and social structure of German minority, as well as aspects related to the assessment of the assimilation process. The article is based primarily on Ukrainian source compilations and archive materials. It also contains a short description of the current status of German minority in the independent Ukraine.
Keywords: national minorities; German minority; Ukraine; mniejszości narodowe; mniejszość niemiecka; Ukraina